Students' Mathematical Logical Thinking in Terms of Learning Style - Muchamad Subali Noto; Mohd Hasril Amiruddin; Siti Maemunah; Marwia Tamrin Bakar; Pipin Sumarni (Department of Mathematics, Universitas Negeri Padang (UNP), 2023)
One of the mathematical abilities that students must have been the ability to think logically. Students' mathematical logical thinking skills are still at a low level, resulting in students having difficulty learning the material given at school, especially straight-line equation material so in solving problems, various mistakes were found by students. This study aims to describe students' logical thinking skills in solving straight-line equation problems based on logical thinking skills and to describe students' learning styles with a thematic approach. This research is a descriptive study with a qualitative approach. This research was conducted randomly with the research subjects of class VIII as many as 20 students filling out the questionnaire and 4 subjects who took the logical thinking ability test, whichconsists of one student with high logical thinking skills, one student with moderate logical thinking skills, one student with thinking skills. low logical thinking, and one student with very low logical thinking skills. The data collection procedure in this study was a description test and a questionnaire to see students' learning styles. The results showed that the average logical thinking ability of students was 61.9 inthe low category and the presentation of student learning styles was 10.8% visual, verbal 11.2%, aural 10.95%, physical 9.4%, logical 10.6. %, social 12.5%, and solitary 10.2%. This research can be carried out by the teacher to determine the students' logical thinking ability in solving the questions they give and can see the student's learning style so that the material presented is well received by students.